Mobile Artificial Intelligence Projects : Develop seven projects on your smartphone using artificial intelligence and deep learning techniques /: Develop seven projects on your smartphone using artificial intelligence and deep learning techniques. (2019) - NG, Karthikeyan; Padmanabhan, Arun; R. Cole, Matt
No abstract available